Randomised, controlled trial of avocado–soybean unsaponifiable (Piascledine) effect on structure modification in hip osteoarthritis: the ERADIAS study. Issue 2 (23rd January 2013) - Maheu, Emmanuel; Cadet, Christian; Marty, Marc; Moyse, Dominique; Kerloch, Isabelle; Coste, Philippe; Dougados, Maxime; Mazières, Bernard; Spector, Tim D; Halhol, Hafid; Grouin, Jean-Marie; Lequesne, Michel
Abstract : Objective: To assess the ability of avocado–soybean unsaponifiable—Expanscience (ASU-E) to slow radiographic progression in symptomatic hip osteoarthritis (OA). Methods: Prospective, randomised, double blind, parallel group, placebo controlled 3 year trial. Patients with symptomatic (painful ≥1 year, Lequesne Index between 3 and 10) hip OA (American College of Rheumatology criteria) and a minimum joint space width (JSW) of the target hip between 1 and 4 mm on a pelvic radiograph were randomly assigned to 300 mg/day ASU-E or placebo. Standing pelvis, target hip anteroposterior (AP) and oblique views were taken annually. The primary outcome was JSW change at year 3, measured at the narrowest point on pelvic or target hip AP view (manual measure using a 0.1 mm graduated magnifying glass). The full analysis dataset (FAS) included all patients having at least two successive radiographs. An analysis of covariance Mixed Model for Repeated Measurements with Missing at Random (for missing data) was performed to compare adjusted 3 year JSW changes (primary outcome) and the percentages of 'progressors' (JSW loss≥0.5 mm) between groups. Results: 399 patients were randomised (345 kept in the FAS), aged 62 (35–84) years, 54% women, mean body mass index 27 (SD 4) kg/m 2, mean symptom duration 4 (SD 5) years, 0–100 normalised Lequesne Index 30 (SD 9) and global pain visual analogue scale 37 (SD 23) mm. Mean baseline JSW was 2.8 (0.9) mm. There was no significant difference on mean JSW loss (−0.638 mm vs −0.672 mm, p=0.72, in the ASU-E and placebo groups, respectively) but there were 20% less progressors in the ASU-E than in the placebo group (40% vs 50%, respectively, p=0.040). No difference was observed on clinical outcomes. Safety was excellent. Conclusions: 3 year treatment with ASU-E reduces the percentage of JSW progressors, indicating a potential structure modifying effect in hip OA to be confirmed, and the clinical relevance requires further assessment. Trial registration number on ClinicalTrial.gov: NCT01062737